The efficacy and safety of sacituzumab govitecan in the treatment of breast cancer: a systemic review and meta-analysis of emerging clinical data - Jiang, Lili; Dai, Youran; Li, Man; Zhao, Zuowei (Frontiers in Immunology, 2025)
IntroductionSacituzumab govitecan (SG) as an antibody-drug conjugate targeting Trophoblast cell surface antigen 2, has emerged as a promising therapy for breast cancer. However, the efficacy of SG across disease subtypes, treatment settings, and in combination regimens remains incompletely defined.Materials and methodsA comprehensive literature search was conducted in PubMed, Embase, Web of Science, and the Cochrane Library to identify studies reporting the clinical efficacy and safety outcomes of SG in breast cancer. Pooled analyses were performed for overall response rate (ORR), progression-free survival (PFS), overall survival (OS), and treatment-related adverse events (AEs). Subgroup analyses were performed by molecular subtype, disease stage, and treatment regimen.ResultsA total of 13 studies involving 2,447 patients with breast cancer were included. SG significantly improved ORR (OR = 3.97, 95%CIs: 1.32-11.90) and OS (HR = 0.59, 95%CIs: 0.47-0.75) versus single agent chemotherapy in RCTs, with pronounced benefit in metastatic triple-negative breast cancer (mTNBC) (ORR = 10.55; HR for OS: 0.50, 95%CIs: 0.43-0.58). Pooled median PFS (mPFS) was 4.95 months (95%CIs: 4.36-5.61months) in RCTs and 5.93 months (95%CIs: 4.76-7.39 months) in single-arm studies, with early-stage TNBC achieving mPFS up to 9.50 months (95%CIs: 8.91-10.13 months). Combination with immunotherapy suggested numerically longer survival (median OS 18.0 vs 12.2 months). The most frequent grade ≥3 AE was neutropenia, occurring in 26-57% of patients, with overall toxicity manageable and consistent across studies.ConclusionsSG provides substantial clinical benefit in breast cancer, improving ORR, OS, and PFS, particularly in TNBC, with consistent efficacy across monotherapy and combination regimens. The increased risk of hematologic and gastrointestinal toxicities warrants careful monitoring in clinical practice.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251072321.